Anterior abdominal wall abscess as a complication of appendicular mass in elderly - Mohamad, Ikhwan Sani; Che Alhadi, Shahidah; Abu bakar, Norzila; Zakaria, Zaidi (OMICS International, 2013)
Appendicitis in the elderly continues to be a challenging surgical problem. Patients usually present late with atypical presentations. The diagnosis of appendicitis is often difficult to establish and there are increased rate of perforation and mortality. Abscess formation with extension to anterior abdominal wall as reported in this case is rather rare. Older patients also tend to undergo more complicated operative procedures and higher rate of postoperative morbidity and mortality. We reported a case of atypical presentation of appendicitis as anterior abdominal abscess and postoperative challenges in geriatric surgery.